2013
DOI: 10.1094/pdis-07-12-0700-re
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Virulence, and Distribution of Two Biovars ofPseudomonas syringaepv.actinidiaein New Zealand

Abstract: Pseudomonas syringae pv. actinidiae, the causal agent of bacterial canker of kiwifruit, was detected for the first time in New Zealand in November 2010. Only in Bay of Plenty, one of the four regions where this pathogen had been detected, did symptoms evolve beyond leaf spots, resulting in cane die-back, wilting of canes, and canker, sometimes leading to death of the vine. Molecular analysis (cts haplotype and BOX-polymerase chain reaction [PCR] electrophoretic pattern) of strains isolated from different regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
172
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(177 citation statements)
references
References 31 publications
1
172
0
4
Order By: Relevance
“…actinidiae, the causal agent of bacterial canker of kiwifruit (Actinidia spp. ), is considered to be a pandemic pathogen and has been isolated around the world over the last 30 years (17,18). Vanneste et al (18) suggested classifying these strains into three biovars, biovar 1, biovar 2, and biovar 3, according to phenotypic, pathogenic, and genomic features.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…actinidiae, the causal agent of bacterial canker of kiwifruit (Actinidia spp. ), is considered to be a pandemic pathogen and has been isolated around the world over the last 30 years (17,18). Vanneste et al (18) suggested classifying these strains into three biovars, biovar 1, biovar 2, and biovar 3, according to phenotypic, pathogenic, and genomic features.…”
mentioning
confidence: 99%
“…actinidiae biovar 3 was reported first in China (22) and more recently in Italy in 2008 (23,24). It was then observed elsewhere in Europe (France and Portugal, 2010; Turkey, Switzerland, and Spain, 2011; Germany and Slovenia, 2013, and Greece, 2014 [18,[25][26][27]) and outside Europe, in New Zealand and Chile (18). Pseudomonas syringae pv.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…(Chapman Cunty et al, 2014;Ferrante and Scortichini, 2015;澤田ら,2014a,2014b;Vanneste, personal communication;Vanneste et al, 2013 Chapman et al, 2012;Cunty et al, 2014;Ferrante and Scortichini, 2015;Han et al, 2003;McCann et al, 2013;三好ら, 2012;澤 田 ら,2014a;Takikawa et al, 1989;Vanneste et al, …”
unclassified